2020
DOI: 10.1128/iai.00828-19
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Interleukin-27 in Early Life Compromise Protective Immunity in a Mouse Model of Gram-Negative Neonatal Sepsis

Abstract: Neonates are at increased risk for bacterial sepsis. We established that the immune-suppressive cytokine interleukin-27 (IL-27) is elevated in neonatal mice. Similarly, human cord blood-derived macrophages express IL-27 genes and secrete more cytokine than macrophages from adults. In the present work, we hypothesized that increased levels of IL-27 predispose neonatal mice to more severe infection during Gram-negative sepsis. Serum IL-27 levels continued to rise during infection. Peripheral tissue analysis reve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 68 publications
2
29
0
Order By: Relevance
“…Consistent with this, a virulence factor of Bordetella pertussis upregulates expression of IL-10 in macrophages, thereby suppressing the development of cell-mediated immunity and limiting the clearance of invading pathogens [14]. Therefore, reduction in the IL-27 level promotes bacterial clearance, improves host response, and decreases mortality [15]. The plasma concentration of IL-27 is significantly elevated in murine models of sepsis, as well as in human patients with this condition; accordingly, it is considered to be a potential diagnostic marker for sepsis [16,17].…”
Section: Introductionmentioning
confidence: 68%
“…Consistent with this, a virulence factor of Bordetella pertussis upregulates expression of IL-10 in macrophages, thereby suppressing the development of cell-mediated immunity and limiting the clearance of invading pathogens [14]. Therefore, reduction in the IL-27 level promotes bacterial clearance, improves host response, and decreases mortality [15]. The plasma concentration of IL-27 is significantly elevated in murine models of sepsis, as well as in human patients with this condition; accordingly, it is considered to be a potential diagnostic marker for sepsis [16,17].…”
Section: Introductionmentioning
confidence: 68%
“…Combination with above the results of HLA-DR expression, this study implies that the therapeutic strategies at early stage in pediatric patient with sepsis should base on the effective treatment to proin ammatory reaction and suppressing the damage resulting from the immune response to infection. IL-27, as a new member of IL-12 family, plays duel-functions in the immune and in ammation reactions [10,29]. IL-27 exerts duel-regulation effects on Th1 cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…As a member of IL-12 family of cytokines, IL-27 signals through a heterodimeric receptor complex consisting of the common IL-6 receptor chain gp130 and a unique IL-27 receptor α chain (IL-27R) WSX-1 [9]. By acting on various immune cells including T cells, B cells, macrophages and dendritic cells, IL-27 presents as pleiotropic cytokine in both pro-in ammatory and anti-in ammatory [10,11]. Studies has suggested that IL-27 could be a diagnostic biomarker for predicting bacterial infection in sepsis patients [12], and the blocking of IL-27 function could be used as a therapeutic strategy of sepsis [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to macrophages, MDSCs have recently been found to be abundant producers of IL-27 in the spleen and blood of murine neonates [ 41 , 64 ]. MDSCs have potent immunosuppressive function and can be categorized into two subsets: monocytic or granulocytic.…”
Section: Il-27 Regulation In Innate Immunity Of the Neonatal Populatimentioning
confidence: 99%
“…Human CD66 + CD33 + C14 -/Lo MHC-II - granulocytic MDSCs also express IL-27 genes (U npublished data ). While initial research established MDSCs as key regulators of tumor micro-environments and cancer progression [ 81 ], recent studies have begun to elucidate the role of MDSC-derived IL-27 in neonatal immunity during infection [ 41 , 64 ]. MDSCs compromised macrophage control of bacterial growth during co-culture and this was partially dependent on IL-27 [ 41 ].…”
Section: Il-27 Regulation In Innate Immunity Of the Neonatal Populatimentioning
confidence: 99%